Formation of self-confidence in prospective teachers-psychologists through the creative use of media technologies - Кошанова, Мараш; Какабаева, Динара; Абдиркенова, Акбидаш; Токкулинова, Гульнар; Кошанова, Жазира (Pedagogy and Psychology, 2022)
The article examines theoretical and practical approaches and features of the creative use of media technologies to increase the student’s self-confidence. In the course of the study, the views of a number of foreign scientists who dealt with the issues of self-knowledge of the future specialist, and the judgments of Kazakhstani scientists who have made a huge contribution to the improvement of professional competencies are considered. In the creative use of media technologies in various aspects, the analysis of the features of self-regulation of mental mechanisms, self-awareness and self-confidence in cognitive and emotional communication with one’s own self, its essence and the content of the role is carried out. A comparative analysis of the goals and objectives set for students, the significance of the conditions for the development of the social environment and their independent role for identifying skills and abilities to “evaluate” is also carried out. Through “self-realization”, “self-esteem”, “self-determination”, “self-development”, “self-knowledge”, effective use of media technologies, it has been determined that creativity is a way of building self-confidence.